Design Considerations of Reconfigurable CMOS Mixers for Multi-Standard Communication Receiver Systems - Manoj Kumar Vishnoi; Satya Sai Srikant (Institute of Advanced Engineering and Science, 2018)
This paper has been carried out the study of reconfigurable wide-band mixers that can do the frequency conversion and gain variation standards with low noise and high linearity used in multi-mode and multi-standard receivers. Over the last few years reconfigurability has become very popular in adopting technology to meet the wideband wireless communication specifications that is compatible with multi-standards like GPS (1.57 GHz), WLAN (2.4 GHz - 5.9 GHz), Bluetooth (2.402 – 2.483 GHz) and ZigBee (0.784 - 0.915 GHz) in low power consumption environment. The reconfigurability can be achieved between low and high band modes through power switching in RF frequency mixers. It can be achieved by flipping the input RF signal between gate and source terminal of input transistor and altering the trans-impedance stage output. With the concept of reconfigurable transistor pair with open and short circuit stubs, one can not only find the configurable gain with center frequencies 7.355, 8.65, 11.35 and 12.65 GHz but also with high power efficiency. Tow Thomas Bi-Quad Topology other than the traditional current commuting technique for the second order trans-impedance amplifier stage, works as a current mode filter over a tunable bandwidth. The active Gilbert mixers are used widely in most of communication system, due to its significance gain, perfect isolation, and linearity in response.